2021
DOI: 10.1590/2175-7860202172137
|View full text |Cite
|
Sign up to set email alerts
|

Asteraceae family: a review of its allelopathic potential and the case of Acmella oleracea and Sphagneticola trilobata

Abstract: Asteraceae family is as an interesting target for researching natural alternatives for crop protection. Many species from this family grow as weeds, and some of them can influence the development of other species by the allelopathy phenomenon. This paper aimed to review the literature for the main genera and species of the Asteraceae family with allelopathic or phytotoxic potential, as well as the classes of secondary metabolites present in this family and responsible for such activity. Artemisia, Ambrosia, Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Among the members of the Asteraceae family, there is a notorious proportion of adventive species (Pyšek, 1998). The reason behind this is partly the fact that many of these species are used as ornamental plants (Araújo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the members of the Asteraceae family, there is a notorious proportion of adventive species (Pyšek, 1998). The reason behind this is partly the fact that many of these species are used as ornamental plants (Araújo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among the members of the Asteraceae family, there is a notorious proportion of adventive species (Pyšek, 1998). The reason behind this is partly the fact that many of these species are used as ornamental plants (Araújo et al, 2021). On the other hand, a more detailed examination of invasive species within the family has revealed that they possess several biological characteristics that can confer advantages in successful invasive processes over native species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asteraceae comprises an interesting group of plants that are viewed as natural alternatives for crop protection. The majority of the members in the family have allelopathic properties, and hence may offer crop protection [ 42 ]. Most of the plant species reported were herbs (59%), which is similar to a study by Skenjana and Poswal [ 20 ], where the majority of the plants reported to be used for pest control in cabbage were herbs.…”
Section: Resultsmentioning
confidence: 99%
“…In India, jambù is used as an aphrodisiac to increase desire and improve a man’s sexual function [ 31 ]. Its range of applications in traditional medicine is wide and includes other uses such as tonic, anticonvulsant, antifungal, antiprotozoal, antidiarrheal, antimalarial, antiulcer, antipyretic, diuretic, anti-inflammatory, diuretic, and insecticide [ 27 , 31 , 62 ].…”
Section: Ethnobotanical Usesmentioning
confidence: 99%